Multistage targeting and dual inhibiting strategies based on bioengineered tumor matrix microenvironment‐mediated protein nanocages for enhancing cancer biotherapy. Issue 2 (5th January 2022) - Hu, Fabiao; Deng, Changping; Zhou, Yiwen; Liu, Yuping; Zhang, Tong; Zhang, Peiwen; Zhao, Zhangting; Miao, Hui; Zheng, Wenyun; Zhang, Wenliang; Wang, Meiyan; Ma, Xingyuan
Abstract: Regulation of the apoptotic pathway plays a critical role in inducing tumor cell death and circumventing drug resistance. Survivin protein is the strongest inhibitor of apoptosis found so far. It is highly expressed in several cancers and is a promising target for cancer therapy. However, clinical applications are limited by incomplete inhibition of survivin expression. Here, we present a novel strategy that extended the release of YM155 (an effective survivin inhibitor that works by inhibiting the activity of survivin promoter) and TATm‐survivin (T34A) (TmSm) protein (survivin protein mutant with penetrating peptide, a potential anticancer protein therapeutic) via tumor matrix microenvironment‐mediated ferritin heavy chain nanocages (FTH1 NCs), enabling significant inhibition of survivin activity at both transcript and protein levels. FTS (FTH1‐matrix metalloproteinase‐2‐TmSm)/YM155 NC synthesis was easily scaled up, and these NCs could sequentially release TmSm protein through matrix metalloproteinase‐2 and promote YM155 to enter the nucleus via transferrin receptor 1 (TfR1) binding, which increased the cytotoxicity and apoptosis of Capan‐2 and A549 cells compared to that with individual drugs. Moreover, FTS/YM155 NCs enhanced drug accumulation at tumor sites and had a higher tumor inhibition rate (88.86%) than the compounds alone in A549 tumor‐bearing mice. In addition, FTS/YM155 NCs exerted significant survivin downregulation (4.43‐fold) and caspase‐3 upregulation (4.31‐fold) and showed better therapeutic outcomes without inducing organ injury, which highlights their promising future clinical application in precision therapy. This tumor microenvironment‐responsive platform could be harnessed to develop an effective therapy via multilevel inhibition of cancer targets.